Photocatalytic asphalt mixtures: Semiconductors’ impact in skid resistance and microtexture - Rocha Segundo, I. (2018)
Photocatalytic and self-cleaning asphalt mixtures have the capacity of mitigating air quality problems and degrade oils/greases. Their functional characteristics can change due to the presence of semiconductors. Thus, after the application of semiconductors on asphalt mixtures, the assessment of skid resistance and microtexture becomes important since they are essential to assure safety. Photocatalytic and self-cleaning were provided to two types of mixtures by spraying and bulk incorporation. Pendulum Tests were carried out in AC 14 and AC 6 at 5 temperature levels in dry and wet conditions. Their microtexture was evaluated by optical non-contact rugometric characterization. The results show that, in dry condition, the skid resistance of functionalized asphalt mixtures was similar to the mixes without treatment. In wet condition, the functionalization caused a maximum decrease of 7% in skid resistance. The semiconductors influenced only the skewness of AC 14 with 6% TiO2 when bulk incorporated. All the other amplitude parameters were not affected by the functionalization. Futhermore, the application of the semiconductors can be used without high impacts in microtexture and therefore in friction.